THE ANALYSIS STUDY OF RENAL TRANSPLANTATION BENEFITS PATIENTS WITH END-STAGE RENAL DISEASE BY IMPROVING ERECTILE FUNCTION: A COMPREHENSIVE SYSTEMATIC REVIEW - Muhammad, Riza Fadhila; Rafi, Muhammad Faiz Haidar (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Renal transplantation is a highly effective treatment for end-stage renal disease (ESRD), addressing the impact of erectile dysfunction on quality of life. Erectile dysfunction, characterized by the inability to achieve and sustain an erection for good sexual activity, affects the physical and psychological well-being of individuals and their partners. However, research on the impact of renal transplantation on erectile dysfunction has yielded conflicting results. Understanding the beneficial impacts of renal transplantation on erectile dysfunction could potentially lead to more successful outcomes. Methods: Adhering to the PRISMA 2020 standards, this systematic investigation sought to examine complete English literature texts published from 2004 until 2024. Only editorials and review articles that had a Digital Object Identifier (DOI) and were published in the same magazine as the submission were considered for acceptance. We utilized many sources, such as ScienceDirect, PubMed, and SagePub, to acquire the literature. Result: The study examined over 40 papers sourced from reliable venues like Science Direct, SagePub, and PubMed. After selecting eight papers for further scrutiny, a comprehensive analysis of the complete corpus of literature was conducted. Conclusion: Renal transplantation has shown significant improvement in erectile function in patients with end-stage renal disease (ESRD), with a lower prevalence of erectile dysfunction and higher function scores. Factors such as pretransplantation IIEF-5 score, age, and anastomosis to the common iliac artery have significant associations with improved erectile function. However, the exact mechanism behind this effect remains unclear.